Improvement of characteristics of the ring input device of the aviation power plant with the screwfanter - Олег Володимирович Жорник (National Aerospace University «Kharkiv Aviation Institute», 2021)
The article considers the method of improving the characteristics of the ring inlet device, taking into account the influence of the propeller of an aircraft power plant with a turboprop engine. It is shown that increasing the total pressure loss in the inlet device by 5% increases, approximately, the specific fuel consumption by 3% and reduces engine thrust by 6%, and uneven flow at the inlet to the engine is the cause of unstable compressor of the turboprop engine. It is proposed to improve the characteristics of the input device by modifying the shape of its shell and channel. Evaluation of the influence of the shape of the shell and the channel of the annular axial VP on its main aerodynamic characteristics, taking into account the non-uniformity of the flow on the fan in the calculated mode of operation of the SU is carried out by calculating the full pressure recovery factor. The object of the study is an annular axial input device in front of which is a coaxial fan turboprop fan. The process of modeling the influence of the shape of the shell and the channel on the recovery factor of total pressure, circular and radial non-uniformity of the flow through the input device is implemented in the software system of finite element analysis ANSYS CFX. Geometric models of coaxial screw fan, fairing and inlet device are built in ANSYS SpaceClaim and transferred using the built-in import function in ANSYS Workbench. Block-structured grid models of air propellers of the first and second rows of the fan in the amount of 1.9 million, fairing and inlet device, in the amount of 3.9 million, are built in the ANSYS TurboGrid environment. The standard Stern (Shear Stress Transport) Gamma Theta Transition was used to close the Navier-Stokes equation system. Based on the results of mathematical modeling of flow in coaxial fans and subsonic ring inlet device on the maximum cruising mode of the turboprop engine, the full pressure recovery factor is calculated and it is established that the most influential factor that increases its full pressure recovery factor.